Analyzing the response to traffic accidents in Medellín, Colombia, with facility location models (2016)
ABSTRACT: In this paper we analyze the emergency medical service (EMS) devoted to attend the victims of traffic accidents in Medellín (Colombia). This work was motivated by the steep increase in injuries derived from these events over the last years. This project has been developed in a partnership with the local authorities of Medellín. In our analysis we used several facility location models to evaluate different courses of improvement. The impact of the proposed measures (a larger fleet of ambulances and different alternatives for their location) is evaluated in terms of the reduction in the number of uncovered districts, the decrease in the busyness of the system, and the resulting improvement in the quality of service. The results of the analysis suggest that to improve the service of the EMS, it is more important to increase the size of the fleet of ambulances than to change their locations at the fire stations.